Hubungan Sindrom Menopause Dengan Kualitas Hidup Wanita Menopause Di Kelurahan Genuk Kabupaten Semarang - Indah Sulistyowati; Dwi Susilawati (Indonesian National Nurses Association (INNA) of Central Java, 2021)
Menopause is a period of cessation of menstruation that usually occur in women aged 45-54 years, with an average age is 51 years. Menopause is caused by a decrease in estrogen that causing various symptoms called menopausal syndrome. Menopausal syndrome causes discomfort and disrupt daily work that it affects the quality of life. The Purpuse : This study aims to identify the correlation between menopausal syndrome with the quality of life among menopausal woman in Kelurahan Genuk Kabupaten Semarang. This research is descriptive correlative with a cross sectional methode. The sampling technique used total sampling were obtained 182 respondents. Data collected by the MRS questionnaire and the WHOQOL-BREF questionnaire. The results showed that most of the respondents had moderate menopausal syndrome (36.6%), while 14.8% had severe menopausal syndrome. The physical quality of life domain has the highest average value (65.96) whereas the social domain has the lowest average value (59.30). There were correlation between menopausal syndrome and the four domains of quality of life, physical domain (p-value= 0.000; r= -0.498), psychology domain (p-value= 0.000; r= -0.415), social domain (p-value= 0.000; r= -0.273), and environment domain (p-value= 0.000; r= -0.307). Menopausal women are advised to be able to recognize menopausal symptoms that arise and make effective management strategies to reduce complaints so that their quality of life increases.